Individual heterogeneity in fitness in a long‐lived herbivore - Madeleine G. Lohman (Wiley, 2021)
Abstract Heterogeneity in the intrinsic quality and nutritional condition of individuals affects reproductive success and consequently fitness. Black brant (Branta bernicla nigricans) are long‐lived, migratory, specialist herbivores. Long migratory pathways and short summer breeding seasons constrain the time and energy available for reproduction, thus magnifying life‐history trade‐offs. These constraints, combined with long lifespans and trade‐offs between current and future reproductive value, provide a model system to examine the role of individual heterogeneity in driving life‐history strategies and individual heterogeneity in fitness. We used hierarchical Bayesian models to examine reproductive trade‐offs, modeling the relationships between within‐year measures of reproductive energy allocation and among‐year demographic rates of individual females breeding on the Yukon‐Kuskokwim Delta, Alaska, using capture–recapture and reproductive data from 1988 to 2014. We generally found that annual survival tended to be buffered against variation in reproductive investment, while breeding probability varied considerably over the range of clutch size‐laying date combinations. We provide evidence for relationships between breeding probability and clutch size, breeding probability and nest initiation date, and an interaction between clutch size and initiation date. Average lifetime clutch size also had a weak positive relationship with apparent survival probability. Our results support the use of demographic buffering strategies for black brant. These results also indirectly suggest associations among environmental conditions during growth, fitness, and energy allocation, highlighting the effects of early growth conditions on individual heterogeneity, and subsequently, lifetime reproductive investment.